2018
DOI: 10.2478/prilozi-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Epidermal Growth Factor Receptor in Hepatocellular Carcinoma

Abstract: Introduction: Epidermal growth factor receptor (EGFR) signaling plays an important role in various cancers, including hepatocellular carcinoma (HCC). We aimed to evaluate immunoexpression of EGFR in HCC and surrounding non-tumor liver tissue and to correlate it to multiple clinicopathologic data. Material and Methods: We analyzed 60 patients with HCC for multiple clinicopathologic characteristics and survival. Presence of the immunosignal and the percentage of positive tumor cells at the whole tumor tissue sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…5 Epidermal growth factor receptor (EGFR) immunoexpression was determined in tissues from patients with HCC, with a mean value of 39.58%, by immunohistochemical (IHC) staining. 6 EGFR immunoexpression is essential for the efficacy and prognosis of patients with HCC to pay attention to the immunoexpression of EGFR in the progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 Epidermal growth factor receptor (EGFR) immunoexpression was determined in tissues from patients with HCC, with a mean value of 39.58%, by immunohistochemical (IHC) staining. 6 EGFR immunoexpression is essential for the efficacy and prognosis of patients with HCC to pay attention to the immunoexpression of EGFR in the progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR is overexpressed in 68–96% of HCC cases, while mutations occur in only 1% of cases ( 34 - 36 ). A study has shown that EGFR expression is closely related to the degree of differentiation, proliferative activity, incidence of intrahepatic metastasis, and prognosis of HCC patients, with high EGFR expression possibly indicating poor prognosis in HCC patients ( 37 ). Song et al .…”
Section: Erbb Family Members In Hcc: Expression and Mechanism Pathwaysmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR), a transmembrane tyrosine kinase receptor, upon ligand binding, activates many diverse signaling pathways, which play a role in cell proliferation, differentiation, and survival [9,10]. Overexpression of EGFR is reported in many cancers including HCC and high expression is correlated to advanced stage and shorter survival [11,12]. EGFR targeted therapies, monoclonal antibodies and small molecule tyrosine kinase inhibitors have given some benefits to patients with HCC [8], so additional research on EGFR immunoexpresion and EGFR mutations is still needed, especially in parts of the world where it has not been done yet.…”
Section: Introductionmentioning
confidence: 99%